HIGH FREQUENCY CLONAL PROPAGATION AND MICRORHIZOME INDUCTION OF CURCUMA LONGA L. (CV LAKADONG)- A RICH SOURCE OF CURCUMIN OF NORTH EAST INDIA - INDRANI SARMA; A. C. DEKA; S. SARMA; T. C. SARMA (The Bioscan, 2011)
A simple in vitro protocol has been developed for efficient plant regeneration and microrhizome induction from axillary buds of Curcuma longa L. The best response for shoot multiplication (19.40±0.51 shoots/ per explant) within 4 weeks was observed in MS medium supplemented with BAP (2.0 mgL-1), NAA (1.0 mgL-1) and 3.0% (w/v) sucrose. A maximum of (100.00±0.71%) root induction were obtained for the plant in MS medium supplemented with NAA (1.0 mgL-1) with reduced level of sucrose (2%). The optimum concentration of sucrose was found to be 6% for the production of microrhizomes on ½ strength MS basal medium supplemented with BAP (5.0 mgL-1) and NAA(0.5 mgL-1) after 4 weeks of culture in microrhizome induction media with an average weight of 2.03g. Larger microrhizomes performed better under in vivo conditions and developed shoots readily, when they were transferred directly from in vitro to soil without acclimatization. Microrhizomes produced under in vitro conditions can be stored and transported easily which are advantageous for in vitro shoot multiplication.